Are the Antarctic dipteran, Eretmoptera murphyi, and Arctic collembolan, Megaphorura arctica, vulnerable to rising temperatures?. Issue 4 (August 2014) - Everatt, M.J.; Convey, P.; Worland, M.R.; Bale, J.S.; Hayward, S.A.L.
Abstract Polar terrestrial invertebrates are suggested as being vulnerable to temperature change relative to lower latitude species, and hence possibly also to climate warming. Previous studies have shown Antarctic and Arctic Collembola and Acari to possess good heat tolerance and survive temperature exposures above 30 °C. To test this feature further, the heat tolerance and physiological plasticity of heat stress were explored in the Arctic collembolan, Megaphorura arctica, from Svalbard and the Antarctic midge, Eretmoptera murphyi, from Signy Island. The data obtained demonstrate considerable heat tolerance in both species, with upper lethal temperatures ≥35 °C (1 h exposures), and tolerance of exposure to 10 and 15 °C exceeding 56 days. This tolerance is far beyond that required in their current environment. Average microhabitat temperatures in August 2011 ranged between 5.1 and 8.1 °C, and rarely rose above 10 °C, in Ny-Ålesund, Svalbard. Summer soil microhabitat temperatures on Signy Island have previously been shown to range between 0 and 10 °C. There was also evidence to suggest that E. murphyi can recover from high-temperature exposure and that M. arctica is capable of rapid heat hardening. M. arctica and E. murphyi therefore have the physiological capacity to tolerate current environmental conditions, as well as future warming. If the features they express are characteristically more general, such polar terrestrial invertebrates will likely fare well under climate warming scenarios.